Environmental ethics: An African understanding - Ojomo P. A (African Journal of Environmental Economics and Management, 2019)
Global concerns about the current environmental crisis have culminated into some controversial environmental ethical theories, that is, normative environmental ethics, sentientist ethics, biocentric ethics, ecocentric ethics and eco-feminist ethics. One of the fundamental underlying features connecting these environmental ethical theories is their grounding in Western perspectives and cultural experiences. Given that environmental concerns are global concerns, and that the imperative of environmental ethics is challenging those life-threatening concerns, critical explorations of environmental ethics need to go beyond the Western horizon. But with respect to the African perspective to environmental ethics and the people’s cultural understanding of the environmental crisis, little has been done in this penultimate area. However, Segun Ogungbemi and Godfrey Tangwa have pioneered philosophical discussions on environmental ethics from an African vantage point. Hence, Ogungbemi defends what he calls “ethics of nature-relatedness,” while Tangwa proposes “eco-bio-communitarianism” as a definitive theory of an African orientation to environmental ethics. This paper is therefore a contribution to the consolidation of an African orientation to environmental ethics through a critique and reconstruction of some of the misrepresentations of the African perspective to the environment, implicit in the arguments of Ogungbemi and Tangwa.